Studi Numerik Pembakaran Butana (C4H10) dalam Meso Scale Combustor dengan Perforated Plate - Baananto, Fauzan; Yuliati, Lilis; Hamidi, Nurkholis (Jurnal Rekayasa Mesin, 2018)
This research was conducted to determine the combustion stability and flame temperature inside meso-scale combustor with variations of perforated plate flame holder and combustion gas temperature at combustor exit side using numerical method or Computational Fluid Dynamics (CFD). Meso-scale combustor is made of two pieces of quartz glass tube with a length of 20 mm and 10 mm. Each quartz glass tube having an internal diameter of 3.5 mm and a wall thickness of 0.7 mm. Two kinds of perforated plate flame holder made of copper i.e. perforated plate type I and perforated plate type II, inserted between two quartz glass tubes. Butane (C4H10) and air were used in this study as fuel and oxidizer, respectively. Numerical simulations were performed using ANSYS Fluent 17.0. The result of numerical simulation showed that the most stable combustion is obtained in meso-scale combustor by using flame holder in the form of perforated plate type II at higher reactant velocity. In addition, the combustor with perforated plate flame holder type II also produces a higher flame temperature at the same reactant speed. These phenomena occured due to the temperature distribution into the reactans is more uniform and the recirculation heats into the reactans is better than the combustor with perforated plate flame holder type I. Flame and combustor walls temperatures increased with increasing recirculation heats.